THE EARLY PERIOD OF CREATIVITY OF ASIA DJEBAR - Yahyokulova Nigora Shukhratovna (International Journal of Innovations in Engineering Research and Technology, 2021)
The approach of modern Algerian writers is based on a conscious relationship with the text, and for most of them, based on reality and an autobiographical project, which is often consistent with it, it goes beyond them. Assia Jabar, the first French-language writer to join the French Academy in 2005. Assia Jabar's work often begins with the individual, even with an autobiographical, to spark collective themes. She repeatedly depicted the situation of her generation, encountering the values of two society and two cultures. In this article, we mainly focus on the first period of Assia Djebar 's work.